2021
DOI: 10.3390/jcm10020204
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Association of Micronutrients Deficiencies during Pregnancy and Neonatal Outcome among Women after Bariatric Surgery

Abstract: Little is known about the association of micronutrients deficiencies during pregnancy and neonatal outcome among women after Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG). We present a prospective study of 87 consecutive women with a history of RYGB (n = 37) or SG (n = 50) who underwent complete and regular clinical and biological nutritional assessments during pregnancy. Data on maternal characteristics, biological nutritional parameters, antenatal management, and perinatal outcome were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…-Deficiencies of vitamins and microelements, especially iron, vitamin B12, A, phylloquinone, and folic acid [75][76][77], as well as zinc, selenium, and vitamins A1, B1, B6, and C [78]; -Hormonal changes-an increase in the level of sex hormone binding globulins (SHBG), progesterone, and estradiol and a decrease in the level of androgens, androstenedione, and testosterone; LH and FSH remained unchanged; studies on anti-Mullerian hormone (AMH) are inconsistent [55,77]; -Improvement in the regularity of menstrual cycles and fertility [77]; -Lower risk of gestational diabetes [9,12,76,79,80] but a higher risk of hypoglycemia and hyperglycemia [81]; -Lower risk of gestational hypertension [9,12,76,79,80,82]; -Higher risk of anemia [9,76]; -Higher risk of fractures [9]; -No effect on gestational weight gain [83].…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%
“…-Deficiencies of vitamins and microelements, especially iron, vitamin B12, A, phylloquinone, and folic acid [75][76][77], as well as zinc, selenium, and vitamins A1, B1, B6, and C [78]; -Hormonal changes-an increase in the level of sex hormone binding globulins (SHBG), progesterone, and estradiol and a decrease in the level of androgens, androstenedione, and testosterone; LH and FSH remained unchanged; studies on anti-Mullerian hormone (AMH) are inconsistent [55,77]; -Improvement in the regularity of menstrual cycles and fertility [77]; -Lower risk of gestational diabetes [9,12,76,79,80] but a higher risk of hypoglycemia and hyperglycemia [81]; -Lower risk of gestational hypertension [9,12,76,79,80,82]; -Higher risk of anemia [9,76]; -Higher risk of fractures [9]; -No effect on gestational weight gain [83].…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%
“…They found no cases of deficiency, no differences between the different techniques, and no effects on maternal and foetal outcomes [ 93 ]. In a prospective study in 87 women [ 179 ], zinc deficiency (<0.51 mg/L) was found in 8.0%, all after RYGB (18.9% vs. 0% in SG; p = 0.02), and preterm birth occurred in 100% of these cases. The usual multivitamins do not provide sufficient zinc for pregnancy after bariatric surgery, especially in the case of malabsorptive techniques.…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%
“…Selenium serum levels were low in 77.8%, 22.2%, and 50.0% in the first, second, and third trimesters, respectively. In a prospective study in 87 women [ 179 ], selenium deficiency (<60 μg/L) was found in 17.2%: 21.6% after RYGB and 14.0% after SG ( p = 0.36). A selenium deficit in the second trimester in women with a history of BS was negatively correlated with birthweight and with birthweight z-score [ 179 ].…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%
“…Protein, iron, folate, calcium, and vitamin B12 and D are the most common nutrient deficiencies after gastric bypass surgery, which may also have negative effects on the fetus [ 30 ]. The need for nutrients during pregnancy increases due to fetal growth, and a deficiency in any of them may increase the risk of fetal abnormalities, especially neural tube defects [ 31 ].…”
Section: Introductionmentioning
confidence: 99%